Medicine on the margins: learning opportunities for undergraduates within inclusion health. Issue 1 (2nd January 2021) - Sharman, Monica; Clark, Emily; Gure-Klinke, Heidi; Player, Emily; Clarry, Clodagh
ABSTRACT: Marginalised groups, including the homeless, refugees and asylum seekers, often experience extremely poor health and present unique challenges to health systems. Undergraduate medical placements with specialist primary care services for these groups can be an insightful learning opportunity within 'inclusion health', a field committed to improving health of these populations. The aim of this project was to showcase organisations for students to gain further exposure and evaluate students' elective experiences at a specialist primary care service for marginalised groups. Students created a mind map to identify organisations in Norwich that were valuable for future students to explore. Five elective students were asked to complete qualitative questionnaires about their experiences. Approximately 10 organisations accommodated participating medical students. Three of five participants responded to the questionnaire, reporting a beneficial learning experience, enabling students to understand complex needs of marginalised groups. The findings offer creative suggestions of where students can gain further exposure. Evaluation of this elective suggests there is unique value in offering placements with a diverse range of organisations that support marginalised groups. Educators should consider integrating opportunities for debriefing and a structured curriculum. Greater support and resources must be provided to include these services for regular teaching and training.